The Role Of The Cell Surface Proteins Of Burkholderia Pseudomallei In The Serodiagnosis Of Melioidosis And Comparative Serological Proteomic Analysis Of The Humoral Immune Response In Melioidosis - Sheik Abdul Kader, Zainoodin (2006)
Melioidosis adalah penyakit di kalangan manusia dan haiwan yang disebabkan oleh jangkitan bakteria, Burkholderia pseudomallei.